The relationship between religion and risky behaviors among Iranian university students - Ameri, Zahra; Mirzakhani, Fahimeh; Nabipour, Amir Reza; Khanjani, Narges; Sullman, Mark J. M. (Springer, 2016)
One factor that protects an individual from risky behavior is religiosity, which is referred to as a shield against risky behaviors. Belief in God and religion plays an important role in young people’s lives, and in comparison with their non-religious peers. They engage less frequently in risky behaviors, such as violence and sexual relations. The present study investigated the relationship between religiosity and engagement in risky behaviors among students from the Pishva branch of the Islamic Azad University, Tehran Province in Iran. This is a descriptive, analytic cross-sectional study. The sample was comprised of 448 students from different degree majors attending the University. Participants completed two questionnaires, including the Risk-Taking Scale and Duke University Religion Index. The data analyses used one-way ANOVAs and Pearson’s correlations. This study found that students who engaged more often in organized religious activities and had higher intrinsic religiosity were less likely to engage in risky behaviors such as sexual risk taking, careless driving, violence, smoking, along with alcohol and drug abuse. Participants with higher involvement in private religious activities reported lower tendencies for the above-mentioned risky behaviors, except sexual risk taking. The findings of this study indicate that the different dimensions of religiousness are related to students’ tendency to avoid risky behavior. Thus, it appears that religion may have a role to play in preventing risky taking behavior in Iran.
Keywords: Religion; Students; Risky behavior; Iran